Development and validation of risk prediction algorithms to estimate future risk of common cancers in men and women: prospective cohort study - Hippisley-Cox, Julia; Coupland, Carol (BMJ Publishing Group Ltd, 2015)
Objective: To derive and validate a set of clinical risk prediction algorithm to estimate the 10-year risk of 11 common cancers.